The right angular gyrus controls spontaneous eyeblink rate: A combined structural MRI and TMS study. (March 2017) - Nakano, Tamami
Abstract: Spontaneous eyeblink rates vary greatly between people, from several to a few dozen blinks per minute. Nevertheless, it remains unknown which brain region controls generation of spontaneous eyeblinks. To investigate this issue, the present study examined brain anatomy, which reflects inter-individual variability in eyeblink rate using structural magnetic resonance images with voxel-based morphometry (VBM) in 57 participants. The gray matter volume of the right angular gyrus (rAG) was positively associated with an increased eyeblink rate. Next, we examined whether eyeblink rate decreased when activity in the rAG was disrupted by transcranial magnetic stimulation (TMS) with a protocol of continuous theta burst stimulation: TMS of the rAG decreased eyeblink rate by 16%. In contrast, sham stimulation did not significantly affect eyeblink rate. The results from the structural MRI and TMS experiments suggest that the rAG is involved in controlling the generation of spontaneous eyeblinks in humans.